Alternative splicing of TIA‐1 in human colon cancer regulates VEGF isoform expression, angiogenesis, tumour growth and bevacizumab resistance. Issue 1 (20th August 2014) - Hamdollah Zadeh, Maryam A.; Amin, Elianna M.; Hoareau-Aveilla, Coralie; Domingo, Enric; Symonds, Kirsty E.; Ye, Xi; Heesom, Katherine J.; Salmon, Andrew; D'Silva, Olivia; Betteridge, Kai B.; Williams, Ann C.; Kerr, David J.; et al.
Abstract : The angiogenic capability of colorectal carcinomas (CRC), and their susceptibility to anti‐angiogenic therapy, is determined by expression of vascular endothelial growth factor (VEGF) isoforms. The intracellular protein T‐cell Intracellular Antigen (TIA‐1) alters post‐transcriptional RNA processing and binds VEGF‐A mRNA. We therefore tested the hypothesis that TIA‐1 could regulate VEGF‐A isoform expression in colorectal cancers. TIA‐1 and VEGF‐A isoform expression was measured in colorectal cancers and cell lines. We discovered that an endogenous splice variant of TIA‐1 encoding a truncated protein, short TIA‐1 (sTIA‐1) was expressed in CRC tissues and invasive K‐Ras mutant colon cancer cells and tissues but not in adenoma cell lines. sTIA‐1 was more highly expressed in CRC than in normal tissues and increased with tumour stage. Knockdown of sTIA‐1 or over‐expression of full length TIA‐1 (flTIA‐1) induced expression of the anti‐angiogenic VEGF isoform VEGF‐A165b. Whereas flTIA‐1 selectively bound VEGF‐A165 mRNA and increased translation of VEGF‐A165b, sTIA‐1 prevented this binding. In nude mice, xenografted colon cancer cells over‐expressing flTIA‐1 formed smaller, less vascular tumours than those expressing sTIA‐1, but flTIA‐1 expression inhibited the effect of anti‐VEGF antibodies. These results indicate that alternative splicing of an RNA binding protein can regulate isoform specific expression of VEGF providing an added layer of complexity to the angiogenic profile of colorectal cancer and their resistance to anti‐angiogenic therapy. Highlights: K‐Ras mutant colon cancers express a novel splice variant, short TIA‐1 (sTIA‐1). sTIA‐1 controls VEGF isoform expression, increasing angiogenic isoforms. Reversion to full length TIA‐1 (flTIA‐1) is anti‐angiogenic. flTIA‐1 expressing cancer cells are resistant to bevacizumab treatment. TIA‐1 splicing may be a potential biomarker for bevacizumab treatment.